2021
DOI: 10.36263/nijest.2021.01.0278
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fallowed and Cultivated Land Use Systems on the Composition and Abundance of Soil Macroinvertebrates Assemblage in Uruk Osung Community, Akwa Ibom State, Nigeria

Abstract: This study was to assess the effect of fallowed and cultivated land-use systems on the abundance of soil macroinvertebrates assemblage. Collections of soil samples were carried out fortnightly twice a month for four months. The extraction of soil macroinvertebrates was carried out using Berlese-Tullgren funnel extractor, and elutriation technique. The mean values of 6.93+/-0.25 were recorded for pH, 32.08+/-0.52oC for temperature, 15.60+/-1.22 for moisture content, were recorded for fallowed soil, and 4.43+/-0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The soil at the Faculty of Science is alkaline, which, together with the recorded levels of DO and other physico-chemical characteristics and inorganic contents, favoured the taxonomic and individual richness of this site over other sample locations on the main campus of the University of Uyo (Akpan et al, 2020). Bufebo and Elias (2020) and Akpan et al (2021) reported that the taxonomic richness and individual composition, abundance, and diversity of soil dwelling arthropods are linked to soil health, which is determined by its physico-chemical properties. The capture of important soil-dwelling arthropod taxa differed across the two studied sampling techniques.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The soil at the Faculty of Science is alkaline, which, together with the recorded levels of DO and other physico-chemical characteristics and inorganic contents, favoured the taxonomic and individual richness of this site over other sample locations on the main campus of the University of Uyo (Akpan et al, 2020). Bufebo and Elias (2020) and Akpan et al (2021) reported that the taxonomic richness and individual composition, abundance, and diversity of soil dwelling arthropods are linked to soil health, which is determined by its physico-chemical properties. The capture of important soil-dwelling arthropod taxa differed across the two studied sampling techniques.…”
Section: Discussionmentioning
confidence: 91%
“…There were highly scarily vegetative covers in this sampling site due to construction work and other activities. The topsoil at each sampling site is loamy, with farming operations conducted surrounding the sampling sites mostly planting cassava (Manihot esculenta) (Akpan et al, 2021).…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations